A next generation systems environment for the Austrailian Hydrographic Service (AHS) - an update on progress - Jones, Matt; Halls, Ian W. (The International Hydrographic Review, 2016)
In the early 2000s, the Australian Hydrographic Service (AHS) had a Digital Hydrographic Data Base (DHDB) developed and implemented to enable the management of hydrographic data, the generation of multiple hydrographic products and distribution capabilities for these products. In 2011, an evolutionary sustainment initiative commenced to re-invigorate the DHDB capability (and be re-named) to a contemporary capability. This article provides an update to the status of this sustainment initiative.